Numerical simulation of strain localization in multi-pass welded joints with account of residual stresses; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Krektuleva R. A. Raisa Alekseevna (2014, 2014)
Title screen